2020
DOI: 10.1177/0267659119899521
|View full text |Cite
|
Sign up to set email alerts
|

Case series of therapeutic hypothermia for neonatal hypoxic-ischemic encephalopathy during extracorporeal life support

Abstract: Therapeutic hypothermia initiated within 6 hours of birth is currently the standard of care for the management of neonates with hypoxic-ischemic encephalopathy. Neonates undergoing therapeutic hypothermia for hypoxic-ischemic encephalopathy are also at risk for severe respiratory failure and need for extracorporeal life support. The risks and benefits of therapeutic hypothermia for hypoxic-ischemic encephalopathy during extracorporeal life support are still not well defined. We report our experience of a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Epilepsy and cerebral palsy are common complications of HIE, and their inducement is related to permanent damage of central nervous system caused by HIE. In addition, routine hypothermia therapy for HIE children also presents a risk of respiratory failure, which may be associated with oxygen limitation due to hypoxic ischemic events [ 33 , 34 ]. The data of this study confirmed that mild hypothermia therapy combined with GM1 can not only improve the treatment effectiveness of HIE but also reduce the risk of epilepsy, cerebral palsy, and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy and cerebral palsy are common complications of HIE, and their inducement is related to permanent damage of central nervous system caused by HIE. In addition, routine hypothermia therapy for HIE children also presents a risk of respiratory failure, which may be associated with oxygen limitation due to hypoxic ischemic events [ 33 , 34 ]. The data of this study confirmed that mild hypothermia therapy combined with GM1 can not only improve the treatment effectiveness of HIE but also reduce the risk of epilepsy, cerebral palsy, and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%